Examining students’ behavior towards campus security preparedness exercise: The role of perceived risk within the theory of planned behavior - Tan, Kim Lim; Sia, Joseph; Tang, Kuok Ho Daniel (SPRINGER, 2020)
Participating in campus security preparedness exercise (CSPE) is vitally important in addressing potential security threats and preventing critical incidents. The present study investigates the various determinants to predict intention, and actual participation in CSPE using the theory of planned behavior (TPB). We also examined the effect of perceived risk on attitude as an extension of the TPB. Based on 441 valid responses collected from students studying in different institutions of higher learning in Malaysia, the partial least squares equation modeling (PLS-SEM) was used to analyze actual participation in CSPE behavior. The findings suggest that TPB is, indeed, a predictive model for explaining participation in CSPE. Based on the findings, the correlation between perceived risk and attitude is insignificant which leads to our subsequent argument on attitude as autonomous and not affected by one’s perceived risk. Nevertheless, the proposed direct relationship between perceived behavioral control (PBC) and intention behavior is not supported. These findings provide an important theoretical platform for new interventions to further promoting active participation in CSPE. Policy implications for improving CSPE behaviors are provided accordingly.